A case study on DWDM 95.5 Pinoy radio's adoption of a Filipino format - Abraham, Pedro Ricaredo Apollo D. (College of Mass Communication, University of the Philippines Diliman, 1993)
"This is a case study of DWDM 95.5 Pinoy Radio. The study focused on the reasons behind the station's move to adopt an all-Filipino program format and Filipino as their language medium. It further sought the reasons why the all-Filipino format is deemed to have failed and why in spite of this, the station's management opted to stay Filipino with some adjustments in approach, content and style. To find the answers to these queries, interviews were conducted with the station management as well as other key people in DWDM. The points covered included a brief history of the station, its organizational structure, sales, ratings and audience. Interviews were also conducted with three alternative music artists who were associated with DWDM or who were deemed by the researcher as knowledgeable about the present state of the radio and recording industries. Questions about "Filipinization" were asked as well as opinions and beliefs about the events that pertain to Pinoy Radio. Findings pointed out that the primary reason behind the format shift to Filipino is to assist the Filipino artist in competing in a market dominated by American Top-40 music. However, the findings also revealed that the failure of this program format was due to poor audience response and bad ratings. IN reference, the study also dealt with the payola system of record companies and radio stations where the songs to be played and how these were played were dictated by monetary considerations. There was also reference to DWDM being owned by the Iglesia Ni Kristo, which may have been a contributing factor to the problems of the station. In a larger perspective, the findings also showed that the difficulties encountered by DWDm could be traced to centuries of colonial domination. Consequently, the listeners themselves also had difficulty accepting "Filipinization" in radio due to prevailing colonial mentality. Another problem identified was the ownership of recording companies by members of the influential Chinese business community, and the apparent preference of local producers and artists to produce foreign or foreign-sounding music. There was also reference to the need for government intervention to achieve "Filipinization" in the broadcasting industry."